FDA approval of Pfizer-BioNTech: Evaluating the significance of mRNA vaccine approval - Syed Abdullah Monawwer; Raahim Naeem (International Society of Global Health, 2021)
The COVID-19 pandemic has devastated the global demographics, claiming more than 4.8 million deaths globally as of October 2021. Mass vaccination is currently the best defense strategy against the virus, which has led to efforts towards the global distribution of COVID-19 vaccines. However, due to the urgency to inoculate, not all vaccines had received federal endorsement by the Food and Drug Administration (FDA) of the United States of America. The FDA is widely considered one of the foremost authorities on drug safety, which is why their ratification of an mRNA vaccine produced by Pfizer, Inc. and BioNTech is a landmark for vaccinology. Although the vaccine was already in distribution, vaccine hesitancy was exacerbated by the lack of timely FDA approval, resulting in the overall lower than expected vaccination rates. Another detrimental factor was distrust in COVID-19 vaccines, based on the widespread claims of adverse effects, despite the vaccine safety being demonstrated in multiple studies. Not only are these new vaccines on a pace to outperform the traditional attenuated virus vaccines, their underlying technology and the use of the RNA molecule ushers in a new era, in which vaccines can be applied and adjusted quicker and for a broader spectrum of targets.